Análise da contribuição do Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) para a sustentabilidade do assentamento Lagoa da Serra, Caucaia-CE. - Oliveira, Francisco Alberto Bastos (2004)
This study analyzes the contribution of the Programa Nacional de Fortalecimento da Agricultura Familiar (PRONAF) to the sustainability in the settlement Lagoa da Serra in Caucaia (CE). It is based on the conception of family farm and on the new paradigms of sustainable development. It describes the researchers' difficulties in defining a concept of family farm, possibly for the diversity of real situations, but it shows some convergent points: the property, the administration and most of the work is made by the family. It describes the activities of PRONAF and its operacionalization. It shows the results of the study of technical collaboration INCRA/FAO on family farm. It presents the conceptual diversities about sustainable development, being based on the integrated and sustainable local development (DLIS) that has the promotion of the social capital and of the human capital as foundations. It characterizes the life conditions of the beneficiaries' of the program through the occupation and income of the family, health, education, housing and water quality. It investigates the agricultural activities of the program users, the cultivation system and their relationship with the environment, being confronted the beneficiaries' situation before the program and after its implementation. It identifies the level of knowledge of the families about PRONAF. It uses the descriptive research in order to know the process of implementation of the program and the results of the program. It uses primary data collected by the application of questionnaires to the beneficiaries of the program and interviews with the principal involved social actors, such as the financial agents, Union Rural Workers and Municipal Council of Sustainable Development. It includes secondary data from documental research, from official documents of PRONAF and specialized bibliography on family farm and sustainable development. It accomplishes the code, tabulation and statistical analysis through the program Statistical Package for the Social the Sciences (SPSS). It uses the Kappa method for the variable durable consumption goods. It presents the results obtained from the researched variables, identifying that the sustainability, in the settlement, was not totality reached with the implementation of PRONAF, as a differentiated agricultural policy, based on sustainable development.